P163 A qualitative evaluation of the Patients Know Best® (PKB) patient-controlled electronic medical record and communication platform in UK HIV services. (30th June 2016) - Warwick, Zoe; Kerr, Cicely; Nafees, Beenish; Gallop, Katy; Hadi, Monica; Desai, Mitesh; Chaponda, Mas
Abstract : Background/introduction: Patients Know Best® (PKB) is an innovative, patient-controlled, medical record and communication platform aiming to facilitate patient centred care. Aim(s)/objectives: This qualitative service evaluation aimed to gain insight into the utility of PKB and experiences of users: specialist doctors, nurses and people living with HIV (PLWHIV). Methods: Participants were from 7 UK HIV centres that use PKB, 2 with PKB integrated with lab systems allowing automatic upload of blood results. Six doctors, 5 nurses and 4 PLWHIV took part in focus groups or individual interviews, which were audio-recorded and transcribed verbatim. Transcripts were systematically coded using a thematic analysis approach. Results: Participants had on average 1.5–2 years' experience ofusing PKB. PKB was mainly used to send/access lab results (automatically, or via secure messaging) or for other secure messaging e.g. clinicians uploaded clinic communications to GPs, care plans, letters for employment/sick notes, PLWHIV requested new/repeat prescriptions, booked appointments, queried results, symptoms and medication issues. Participants reported that PKB enabled different models of care (e.g. nurse-led, remote-monitoring) and use resulted in efficiencies and increased capacity, improved patient experience and self-management. Communication with GPs, pharmacists and clinicians in other departments via PKB was an area of unmet potential. Participants suggested lack of IT systems integration and resistance to PKB by some colleagues/PLWHIV were barriers to wider uptake. Discussion/conclusion: Varied benefits and value of PKB were reported. Overall experiences with PKB in UK HIV services were positive with all supporting continued use, greater uptake and integration.